Asthma progression and mortality: the role of inhaled corticosteroids. Issue 1 (18th July 2019) - O'Byrne, Paul; Fabbri, Leonardo M.; Pavord, Ian D.; Papi, Alberto; Petruzzelli, Stefano; Lange, Peter
Overall, asthma mortality rates have declined dramatically in the last 30 years, due to improved diagnosis and to better treatment, particularly in the 1990s following the more widespread use of inhaled corticosteroids (ICSs). The impact of ICS on other long-term outcomes, such as lung function decline, is less certain, in part because the factors associated with these outcomes are incompletely understood. The purpose of this review is to evaluate the effect of pharmacological interventions, particularly ICS, on asthma progression and mortality. Furthermore, we review the potential mechanisms of action of pharmacotherapy on asthma progression and mortality, the effects of ICS on long-term changes in lung function, and the role of ICS in various asthma phenotypes. Overall, there is compelling evidence of the value of ICS in improving asthma control, as measured by improved symptoms, pulmonary function and reduced exacerbations. There is, however, less convincing evidence that ICS prevents the decline in pulmonary function that occurs in some, although not all, patients with asthma. Severe exacerbations are associated with a more rapid decline in pulmonary function, and by reducing the risk of severe exacerbations, it is likely that ICS will, at least partially, prevent this decline. Studies using administrative databases also support an important role for ICS in reducing asthma mortality, but the fact that asthma mortality is, fortunately, an uncommon event makes it highly improbable that this will be demonstrated in prospective trials. There is compelling evidence of the value of ICS in improving asthma control and indirect evidence that ICS prevents lung function decline by preventing severe exacerbations. Registry-based studies support the role of ICS in reducing asthma mortality. http://bit.ly/2VcNjaz